2010
DOI: 10.1186/1471-2490-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Lack of awareness of erectile dysfunction in many men with risk factors for erectile dysfunction

Abstract: BackgroundMen with erectile dysfunction often have concurrent medical conditions. Conversely, men with these conditions may also have underlying erectile dysfunction. The prevalence of unrecognized erectile dysfunction in men with comorbidities commonly associated with erectile dysfunction was determined in men invited to participate in a double-blind, randomized, placebo-controlled trial of sildenafil citrate.MethodsMen ≥30 years old presenting with ≥1 erectile dysfunction risk factor (controlled hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…Contrary to literature, in our study we had a predominance of milder forms of dysfunction. 21,30 We emphasize that in patients with CAD the prevalence is higher than in the general population, which was also described by Kloner and Mullin, 31 who identified in this group 75% and 67% of patients with difficulty in having or maintaining an adequate erection, respectively.…”
mentioning
confidence: 73%
“…Contrary to literature, in our study we had a predominance of milder forms of dysfunction. 21,30 We emphasize that in patients with CAD the prevalence is higher than in the general population, which was also described by Kloner and Mullin, 31 who identified in this group 75% and 67% of patients with difficulty in having or maintaining an adequate erection, respectively.…”
mentioning
confidence: 73%
“…The non-typical ED, which includes honeymoon ED (ED accompanying the first sexual attempts), teenager ED, mild ED, unrecognized ED, and WME-NS, is unsuitable to be assessed by the scoring system of IIEF [32] and habitually presumed to be psychogenic origin. But in fact, several studies had shown that early vascular dysfunction and cardiovascular risk factors also occurred in the subjects with honeymoon ED [33], teenager ED [34], mild ED [35] and unrecognized ED [36], which implied that these non-typical ED cohorts might have fairly similar risk factors with the typical ED population. Likewise, the underlying risk factors related to ED in our study also occurred in the WME-NS cohort (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Existen factores de riesgo mutuos (tabaco 16 , diabetes mellitus 17 , enfermedades cardíacas 18---21 y obesidad 22---24 ) compartidos por la DE y la periodontitis crónica 20 .…”
Section: Introductionunclassified